PARAPHRASICAL INTERTEXTUALITY: INTERPRETATION MARKS IN THE SCIENTIFIC ABSTRACT GENRE - Rubia Mara Bragagnollo (Travessias, 2010)
This article aims to analyze a production of the scientific abstract genre, written by a student of 1st year of Arts, at Universidade Estadual de Maring, with the purpose of investigate the existence of marks of paraphrasical intertextuality which leads towards an interpretation of the original text. From the notions of polyphony and dialogism (Bakhtin, 2006), of intertextuality (Koch, 1997), of paraphrase (Fuchs, 1985; SantAnna, 2003) and of scientific abstract (Therezo, 2007) written, added to the analyses carried out, we verified that this genre, despite being paraphrasical, presents marks which denote interpretation, showing so determined level of comprehension in reading.